Innovation in Education : Improving Learning Outcomes through ICT Technology - World Bank (World Bank, Washington, DC, 2020)
Many countries in sub-Saharan Africa identify technology as a viable complementary tool to improve learning outcomes in primary and secondary education. New research evidence from The Gambia suggests that a student-centered computer-assisted learning (CAL) program significantly improves student performance and teaching effectiveness in secondary schools. Policy action to complement traditional pedagogical methods with interactive technology in classrooms can help countries translate their gains in access to education into greater achievements in learning and skills.